Middle east in revolution - Trevelyan, Humphrey (London, 1970)
His book is a first-hand account of diplomacy and action in a period of exceptional difficulty in the Middle East, the first to be written by a British diplomat viewing events from the inside. Lord Trevelyan has no political axe to grind and has written a completely objective account of events which still have their effect upon the present confused and dangerous situation in the Middle East. It is a most readable book which will also be valuable to historians of the period.